A Cocooning Project to Protect Newborns from Pertussis. Issue 3 (June 2014) - Rust, Christina
Abstract The Pertussis Cocooning Project was created through a collaborative effort by a health care organization and a State Department for Public Health to decrease community pertussis rates and protect infants from the deadly effects of pertussis. Free pertussis immunizations are provided to all mothers who give birth at the health care organization and to all infants' family members and caregivers older than 18 years.